A new algorithm to generate non-uniformly dispersed representative volume elements of composite materials with high volume fractions. (July 2022) - Cai, Chaocan; Wang, Bo; Yin, Weilong; Xu, Zhonghai; Wang, Rongguo; He, Xiaodong
Graphical abstract: Highlights: A new method to generate non-uniformly dispersed three-dimensional representative volume elements (RVEs) of composites is proposed. The proposed algorithm can generate RVEs with high volume fractions. Statistical assessment of RVEs are validated by comparison with the microstructure of actual composites. Homogenized elastic properties predicted by finite element method are in good agreements with the experimental data and theoretical models. Realize the parameter coordination of fiber volume fractions and inter-fiber distance. The proposed method can be easily adapted for the exploration of particle-reinforced composites. Abstract: In this work, a novel algorithm is proposed to generate three-dimensional random spatial distribution representative volume elements (RVEs) of composite materials. The approach is based on the bionic optimization technology of Cuckoo search algorithm. It addresses the problem of jamming limitation in the previous approaches and is able to generate nonuniformly dispersed microstructures with high fiber volume fractions and any specified inter-fiber distances. Statistical analysis is implemented to evaluate the nonuniform distributions of the generated RVEs and the results agree well with the experimental data in all statistical distributions. Furthermore, finite element method and volume homogenization are conducted to predict the elastic properties of the generated RVEs. The predictions are close to the experimental data in the literatures and the expected transversal isotropy in the 2–3 plane of the microstructures is confirmed. In addition, the effective elastic properties of glass/epoxy composites with fiber volume fractions of 30–70% are calculated by using the generated microstructures and compared with the theoretical models. The agreement of the numerical and analytical results provides further validation for the proposed algorithm to generate RVEs of composite materials. This method also can be easily used in the exploration of particle-reinforced composites.